Adaptation of Oral Processing to the Fracture Properties of Soft Solids. Issue 1 (28th October 2013) - Koç, H.; Çakir, E.; Vinyard, C.J.; Essick, G.; Daubert, C.R.; Drake, M.A.; Osborne, J.; Foegeding, E.A.
Abstract: Hardness and rubberiness are distinct textural properties that are associated with extended oral processing times and therefore of interest to designing food structure for specific textural properties. Model food gels were developed with (1) increasing strength/hardness and constant deformability or (2) increasing deformability/rubberiness within a limited range of strength. Gel structures were characterized based on mechanical properties and the muscle activity (electromyography) and mandibular movements (three‐dimensional jaw tracking) required for oral processing. Increased strength or deformability required more chewing cycles and increased muscle activity to breakdown samples for swallowing. In contrast, jaw movement amplitude increased in all directions with increased strength and remained constant or decreased with increased deformability. Specific mechanical properties that were correlated with oral processing parameters changed as chewing progressed, possibly reflecting a change in dominate mechanical properties and sensory perception during oral processing. Practical Applications: A fundamental understanding of how food structure determines sensory texture is essential to designing foods that are healthy and desirable to consumers. Oral processing, from first bite through swallowing, is the main physiological element of texture evaluation. Model soft solid foods with increasing strength/hardness or deformability/rubberiness were developed and characterized by mechanical tests and oral processing. Mastication of harder or more deformable structures required different chewing movements in bolus preparation. The specific mechanical properties relating to oral processing may change during the chewing sequence.